From autonomous actors to collaborative professionals: perceptions of co-teaching in a Finnish school community - Ahonen Heini; Franska Niilo; Palonen Tuire; Reinius Hanna; Tiippana Netta; Hakkarainen Kai (Routledge, Taylor & Francis Group, 2025)
This study examined the factors shaping co-teaching within a Finnish primary school's community. The qualitative study was conducted by teacher and principal interviews and teacher surveys. Thematic content analysis revealed five factors establishing the co-teaching practices: providing collegial support, team building, continuous professional development, the intrinsic value of co-teaching, and the structure of the work community. These factors aggregated into two larger arenas: teachers’ sphere of influence and systemic elements -arena, which was experienced to be beyond individual teacher influence. These factors illustrate the complexity of the work community with co-teaching and how they can both complicate and contribute to an educator's daily work. In addition, individual, community and resource-specific challenges regarding co-teaching emerged. Finally, we identified three educator profiles on the involvement in decision-making when developing co-teaching practises. We distinguished pioneers, travelling companions and critical observers as three diverging roles that educators have adopted in influencing the decision-making.